Leading sustainable school improvement: a meta-synthesis of qualitative research on problems and challenges faced by school leaders - Karakose, Turgut; Ozdogru, Mehmet; Malkoc, Nedim (Frontiers in Education, 2024)
IntroductionDeveloping broader insights into the problems or challenges faced by school leaders resulting from various factors both within and out of school is a crucial attempt to provide solutions on scientific grounds and to ensure the sustainability of schools.MethodsThis study aims to contribute to both the theory and practice of sustainable school administration through conducting the meta-synthesis of prior qualitative studies on the problems and challenges faced by school leaders. Data were collected from several databases indexing educational research, and the analysis was conducted using data from 24 studies presenting the perspectives of a total of 614 participants.ResultsThe results showed that school leaders had significant problems particularly with insufficient funds and budgets, shortage of school staff, insufficient or unwilling teachers, an abundance of responsibilities with limited authority, maintenance of school buildings, and tackling excessive and fast-changing legislations. Lack of inspectors’ expertise and their being closed to novel ideas, principal assignments not based on merit, insufficient communication and collaboration among teachers, and pressures from the superiors or unions were also listed among the other serious problems and challenges.DiscussionThese findings suggest putting more effort into improving human resources, school budgets, curriculum and instruction, parental involvement, mechanisms to tackle student problematic behavior, ensuring the professional quality of teachers, school leaders, and inspectors as well as providing school leaders with the necessary support while expecting them to realize an abundance of responsibilities. The challenges caused by bureaucratic pressures, political press, and union discord should also be crucially considered by the higher authorities if school leaders are expected to contribute to the sustainable improvement of schools.